PENGARUH PEMBERIAN MULSA DAN JARAK TANAM PADA HASIL TANAMAN KEDELAI (Glycine max, L. Merrill.) VAR. GROBOGAN - Fasokha Nurbaiti; Gembong Haryono; Agus Suprapto (Universitas Tidar, 2017)
Research on the effect of plant distance and mulch on yield of crop soybean (Glycine max, L. Merrill) Var. Grobogan conducted in November 2016 to January 2017. The study in the village Kembangkuning, District Windusari, Magelang. Altitude of 440 m above sea level, with latosol soil type and soil pH of 6.5. The research method using a factorial (3 x 3) are arranged in a complete randomized block design with three replications. The first factor was kind of mulch, the straw mulch, black plastic mulch silver and black plastic mulch. The second factor was plant distance, the plant distance of 40 cm x 10 cm, 40 cm x 20 cm and 40 cm x 30 cm. Silver black plastic mulch increased plant height, the number of productive branches per plant, weight of 1.000 dry seeds, stover dry weight per plant and dry seed weight per m2. The plant distance of 40 cm x 30 cm increased the number of productive branches per plant, weight of 1.000 dry seeds and stover dry weight per plant. The combination of mulch and plant distance was not effect on all parameters of observation